TINJAUAN HUKUM PIDANA TERHADAP PENYELESAIAN KREDIT MACET BERDASARKAN STUDI KASUS PUTUSAN PENGADILAN NEGERI SENGETI NO. 120/ Pid.B/2016/PN Snt - SUGIHARTOKO, HERI (Dinamika Hukum, 2018)
This thesis aims to analyze the criminal review of the act of forced taking of goods in the debtor's authority by the Debt Collector and the consideration of the judge in Decision No. 120 / Pid.B / 2016 / PN Snt. concerning criminal acts of forced effort carried out by the Debt Collector in accordance with article 368 paragraph (1) of the Criminal Code in conjunction with Article 56 to 1. The background of the research is based on the rampant forced taking of goods controlled by creditors by debt collectors. Forced collection of goods is carried out because of bad credit.The approach method in the study is a case study approach, namely the case of forced taking of goods against creditors by Debt Collector in the decision of the Sengeti District Court Number. 120 / Pid.B / 2016 / PN Snt. The results of the study stated that debt collectors who forcibly take goods in the power of debtor debtors who are not registered are criminal acts that violate the provisions of Article 368 of the Criminal Code, namely acts of extortion, plunder and threats. Debt collector in the consumer financing credit agreement is only a tool and the last effort of the finance company to return the credit object in arrears. Withdrawal of motorized vehicle items is not permitted without the right rights. Judges consider in imposing a verdict on the crime of forcibly taking goods controlled by the creditor in accordance with the provisions concerning criminal acts of extortion carried out jointly, namely in article 368 paragraph (1) jo article 56 paragraph (1) of the Criminal Code. Keywords: debt collector, bad credit, forced collection of goods